A comparison between intravenous paracetamol plus fentanyl and intravenous fentanyl alone for postoperative analgesia during laparoscopic cholecystectomy - Choudhuri, Anirban Hom (Medknow Publications & Media Pvt Ltd, 2011)
PURPOSE: our study compared the effect of fentanyl alone with fentanyl plus intravenous Paracetamol for analgesic efficacy, opioid sparing effects, and opioid-related side effects after laparoscopic cholecystectomy. MATERIALS AND METHODS: eighty patients undergoing laparoscopic cholecystectomy were randomized into two groups, who were given either an IV placebo or an IV injection of 1g paracetamol just before induction. Both groups received fentanyl during induction and IM diclofenac for pain relief every 8 hourly for 24 h after surgery. The postoperative pain relief was evaluated by a visual analog scale (VAS) and consumption of fentanyl as rescue analgesic in the postoperative period for 24 h after surgery was measured. The incidence of PONV and sedation scores was also measured in the postoperative period. RESULTS: the mean VAS score in first and second hour after surgery was less in the group receiving IV Paracetamol (3.3±0.4* vs. 5.2±0.9; 3.1±0.4* vs. 4.3±0.3); the fentanyl consumption over first 24 h was also less in the group receiving IV paracetamol (50±14.9 vs. 150±25.8). The time requirement of first dose of rescue analgesic in the postoperative period was also significantly prolonged in the group receiving IV paracetamol (76±24.7 vs. 48±15.8). There was no difference in the sedation scores and in the incidence of PONV in the two groups. CONCLUSION: The study demonstrates the usefulness of intravenous paracetamol as pre-emptive analgesic in the treatment of postoperative pain after laparoscopic cholecystectomy.